Sistem Alarm untuk Mendeteksi Kedatangan Kereta Api - Andre Goslie; Fikri Tri Fadilah; Supriyadi Supriyadi; Ahmad Nalhadi (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2018)
Accidents can occur anywhere including railroad crossings that are the responsibility of the Transportation Department. Train crossing  on average still using the manual system so that has high potential for  accidents. The design of this tool is used to minimize accidents that occur and increase the awareness of railroad communities pass. The basic design of this tool use the  sensor so the sensor will send a signal) when the train passes. The making of the tool is converted into a system button due to the  long process of permission to the rail party. The making of this tool is in accordance with the advice of the RW Chairman and the officer of the railroad crossing. Alarms and lights will work when the button is pressed and  off according to the predefined timer.